Design of Web-Based Inventory Accounting Information System at PT XYZ - Ranti Rosalina, Resmi; Arifin, Riza; Pasaribu, Johni S (International Journal of Engineering, Science and Information Technology, 2024)
PT XYZ is a company engaged in the retail trade of large and small clothing, and it is located in the city of Bandung. As a trading company, PT XYZ needs to utilize information technology in managing warehouse inventory, which is no longer manual management, namely recording in paper media, which will be susceptible to data discrepancies. The web application here is interpreted as an inventory application through a display that includes goods to be stored in the warehouse and product transactions that come in and out. The research method used here is the interview and observation method. Software creation is carried out with a waterfall model consisting of the following stages: system planning analysis, system analysis, design, implementation, and maintenance. In the object of system modeling with visual data flow diagrams and flowcharts. The results of this study produce web-based software using PHP as a programming language with MySQL as a database and visual code for its program editor. Through this system, it is expected to facilitate work and can be used at any time. This inventory application can be a benchmark for managing incoming and outgoing goods. Another benefit is that this web-based application aims to control the stock of goods at any time.